Exploring Students' Perspectives on the Integration of AI in Chemistry Learning Processes: Opportunities and Challenges - M, Munawwarah; Alqadri, Zulqifli; Zubair, Sakinah (Asian Journal of Science Education, 2025)
This study explores the integration of Artificial Intelligence (AI) in the chemistry learning process, focusing on students' perspectives, opportunities, and challenges. Using a descriptive qualitative approach supported by quantitative methods, data were collected through questionnaires and interviews with 40 chemistry students from Universitas Negeri Makassar. The questionnaire comprised 19 Likert-scale questions and open-ended items addressing four main indicators: effectiveness, interactivity, critical thinking, and independence in learning. Semi-structured interviews were conducted with 20 students to gather in-depth insights into their reasons for using AI, their experiences, and suggestions for AI application in education. The findings highlight the need for a balanced approach to AI integration, ensuring it complements traditional learning methods without replacing human interaction. Recommendations for future research include examining the long-term impact of AI on learning outcomes and exploring strategies to foster independent learning alongside AI usage. This study contributes to understanding the role of AI in education and provides insights for its effective implementation in chemistry learning.